Effects of latent heat storage and controls on stability and performance of a solar assisted heat pump system for domestic hot water production. (1st July 2017) - Youssef, W.; Ge, Y.T.; Tassou, S.A.
Highlights: A test rig of a new indirect solar assisted heat pump (IDX-SAHP) system has been designed, built, instrumented and controlled. The IDX-SAHP system consists of three operational loops: solar thermal, solar assisted heat pump and load profile. A PCM heat exchanger tank was purposely designed and installed in the system solar thermal loop to store solar energy. Comprehensive measurements were carried out on the test rig and system structures with and without the PCM tank. Test results showed that the PCM heat exchanger integration exerted a significant effect on system stability and performance efficiency. Abstract: Solar assisted heat pump systems have been widely applied in domestic hot water productions due to their sustainability and stability in operations. However, their performance efficiency requires further improvement using advanced technologies such as energy storage with phase change materials (PCM) and optimal system controls. Accordingly, a test rig of a new indirect solar assisted heat pump (IDX-SAHP) system has been designed, built and instrumented. The IDX-SAHP system consists of three operational loops: solar thermal, solar assisted heat pump and load profile. A PCM heat exchanger tank was purposely designed and installed in the system solar thermal loop to store solar energy, when applicable, and release heat when required by the heat pump. In addition, an air cooling heat exchanger was also installed in the solar thermal loop to absorb heat from the ambient air for the heat pump. A detailed control strategy has been designed and implemented for the system for efficient operation in different modes and maintain constant load supply water temperature during an operational day. In different weather conditions of sunny and overcast, comprehensive measurements were carried out on the test rig and system structures with and without the PCM tank. Test results showed that the system could efficiently meet the daily domestic hot water demand and the PCM heat exchanger integration exerted a significant effect on system stability and performance efficiency. Quantitatively, the average COP of the IDX-SHAP system with a PCM tank could increase 6.1% and 14.0% on sunny and cloudy days respectively compared to systems without PCM tank integration.